Comparison between incremental conductance and perturb and observe algorithms in photovoltaic system under low temperature and irradiation levels - Abssane, Sara; Outzourhit, Abdelkader; Amatoul, Fatima Zahra (Institute of Advanced Engineering and Science, 2024)
This paper compares two mostly used maximum power point tracking (MPPT) methods, perturb and observe (P&O), and incremental conductance (INC), for a photovoltaic (PV) system integrated with a step-up converter and resistive load. The evaluation was conducted using MATLAB/Simulink under two specific environmental conditions: low irradiation and temperature levels. The results indicate that under irradiation levels below 200 W/m², the INC algorithm outperforms P&O by exhibiting minimal fluctuations and achieving higher efficiency. Conversely, under low temperature (below 25 °C) the P&O method reaches the highest efficiency, exceeding 99%. These findings highlight the importance of selecting the appropriate MPPT algorithm based on specific environmental conditions to optimize the energy output of PV systems.